The Assessment of University Students Knowledge on Academic Writing - Jezhny , Karzan Abdullah; Bapir, Nazenin Shekh Muhemad (Zanco Journal of Human Sciences, 2021)
This study which is entitled "The Assessment of University Students Knowledge on Academic Writing" attempts at exploring the knowledge level of university students with regard to writing in an academic style. Its primary aim is to realize whether university students have knowledge of producing and structuring ideas and thoughts in academic writing process. These two levels of writing, generation and organization of ideas, are reflected in academically written texts. Hence, the significance of the study is to urge university students to cope with the theoretical principles of academic writing. Researchers depend on questionnaire to collect data from 102 third year students in departments of English in College of Education, College of Basic Education and College of Language at Salahaddin University - Erbil. The study, first, is concerned with a brief introduction of the nature of academic writing. Then, it presents the literature review of the study. Following this, the relationship between academic reading and writing is highlighted. The study, also, lays emphasis on elements and features of academic writing. The findings of the study indicate that although students are taught academic writing, they have difficulties in various aspects of academic writing. There are clear deficiencies in their knowledge of structuring an academic text.